Analysis of Factors Influencing Farmers' Decisions in Lemongrass Farming in the City of Solok - Helmayuni; Mardianto; Firnando, Edi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
This research aims to determine the factors influencing farmers' decisions in lemongrass farming in the city of Solok. The method used in this research is a case study method, and sampling is done through census method. The data used are primary and secondary data. The analysis used is Multinomial Logit analysis using SPSS. From the research results, it is known that the significant factors influencing farmers' decisions in lemongrass farming in the city of Solok are the variables of farming experience, the role of agricultural extension officers, and interaction among farmers, while variables such as land area, education level, age, and gender do not significantly affect farmers' decisions in lemongrass farming in the city of Solok. 58.1% of farmers engage in farming out of desire, 32.3% participate due to influence, and 9.7% due to invitation.